2015
DOI: 10.1007/s10596-015-9542-3
|View full text |Cite
|
Sign up to set email alerts
|

Multiphase lattice Boltzmann simulations for porous media applications

Abstract: Over the last two decades, lattice Boltzmann methods have become an increasingly popular tool to compute the flow in complex geometries such as porous media. In addition to single phase simulations allowing, for example, a precise quantification of the permeability of a porous sample, a number of extensions to the lattice Boltzmann method are available which allow to study multiphase and multicomponent flows on a pore scale level. In this article, we give an extensive overview on a number of these diffuse inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
243
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 363 publications
(260 citation statements)
references
References 211 publications
3
243
0
2
Order By: Relevance
“…[46][47][48] As we know, it is still challenging to simulate a wide range of viscosity ratios for many existing multiphase LB models. 30 To examine the range of viscosity ratios that the present model can access, we simulate the displacement of a more viscous fluid by a less viscous one in the heterogeneous pore network at log Ca = −5. The dynamic viscosities of both fluids are chosen as η n = {0.005, 0.01, 0.02, 0.04} and η w = {0.1, 0.3, 0.5} in which η w is limited to not more than 0.5 because as η (or τ) increases, so does the Knudsen number (defined as the ratio of the mean free path to the characteristic length scale).…”
Section: -13mentioning
confidence: 99%
“…[46][47][48] As we know, it is still challenging to simulate a wide range of viscosity ratios for many existing multiphase LB models. 30 To examine the range of viscosity ratios that the present model can access, we simulate the displacement of a more viscous fluid by a less viscous one in the heterogeneous pore network at log Ca = −5. The dynamic viscosities of both fluids are chosen as η n = {0.005, 0.01, 0.02, 0.04} and η w = {0.1, 0.3, 0.5} in which η w is limited to not more than 0.5 because as η (or τ) increases, so does the Knudsen number (defined as the ratio of the mean free path to the characteristic length scale).…”
Section: -13mentioning
confidence: 99%
“…Direct methods for two-phase fluid flow have a significantly higher computational cost than single phase flow models and are typically solved using Lattice Boltzman methods, as these are highly parallel and relatively easy to implement (Dupuis and Yeomans 2004;Gao et al 2012;Kusumaatmaja et al 2006;Yeomans 2007, 2010;Liu et al 2014;Ramstad et al 2010). The Lattice Boltzmann method is slightly different to the more familiar finite volume and finite element methods.…”
Section: Computational and Modelling Challengesmentioning
confidence: 99%
“…Liu et al [14] reviewed simulation of single-phase and multiphase multicomponent flow at pore level using the LB method. They reviewed different LB methods, discussed their advantages and disadvantages, and concluded that one method cannot be necessarily the most preferred one.…”
Section: Focus Of This Special Issuementioning
confidence: 99%